Human rights legal education in times of transition: perspectives and practices of law instructors in Myanmar - Eberbach, Kristina (Human rights review, 2023)
This mixed-methods study examines the human rights and human rights education and training (HRET) perspectives and practices of law educators in Myanmar during the democratic transition that ended with the 2021 coup. “Contextual, Theoretical, and Methodological Framing” provides an overview of legal and human rights education in Myanmar, discusses the potential of human rights education in law schools during democratic transitions, addresses why educators’ human rights and human rights education perspectives and practices are important to examine, and presents the research methodology. “Findings” presents findings based on the two phases of research during the transitional period: phase 1 (2015–2017)—law instructors’ perspectives and practices after participating in a multi-year HRET program; and phase 2 (2019–2020)—law instructors’ perspectives on the goals, challenges, and potential of HRET in Myanmar. The third section—“Discussion and Implications”—examines the contextual challenges and opportunities for human rights education as related to (1) critical human rights education, (2) practice-oriented HRET, and (3) administrative policies and practices for human rights and HRET within universities.